1998
DOI: 10.1038/nbt0898-748
|View full text |Cite
|
Sign up to set email alerts
|

Computer-assisted rational design of immunosuppressive compounds

Abstract: We describe the rational design of immunosuppressive peptides without relying on information regarding their receptors or mechanisms of action. The design strategy uses a variety of topological and shape descriptors in combination with an analysis of molecular dynamics trajectories for the identification of potential drug candidates. This strategy was applied to the development of immunosuppressive peptides with enhanced potency. The lead compounds were peptides, derived from the heavy chain of HLA class I, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(64 citation statements)
references
References 23 publications
0
64
0
Order By: Relevance
“…We have previously reported that Allotrap 1258 modulates heme oxygenase activity in vitro and in vivo (8,12). In animals, peptide therapy resulted in up-regulation of heme oxygenase, and we have speculated that the immunomodulatory activity of Allotrap 1258 may be mediated via effects on HO-1.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We have previously reported that Allotrap 1258 modulates heme oxygenase activity in vitro and in vivo (8,12). In animals, peptide therapy resulted in up-regulation of heme oxygenase, and we have speculated that the immunomodulatory activity of Allotrap 1258 may be mediated via effects on HO-1.…”
Section: Discussionmentioning
confidence: 98%
“…In vivo, they were shown to prolong allograft survival in rodents (2)(3)(4)(5)(6)(7). Based on these HLA-derived peptide sequences, novel immunomodulatory peptides were developed by computer-aided rational design (8). Initially, the biological activity of a panel of 19 peptides derived from peptide 2702.75-84 (HLA-B2702, amino acids 75-84) as well as other major histocompatibility complex molecules was assessed in a heterotopic mouse allograft model.…”
mentioning
confidence: 99%
“…In addition, a novel TNF-␣ inhibitor, RDP58 [131], was successfully used in our laboratory to treat acute and chronic Kollias, and R. Buelow, unpublished results]. RDP58 given orally or intraperitonealy at pharmacologically relevent doses reduced the severity of acute DSS-mediated colitis as judged from clinical and histological improvements.…”
Section: Relevancementioning
confidence: 99%
“…For example, RDP58, a novel d-amino acid decapeptide (r-(nle)3-r-(nle)3-gy-CONH2), which was developed by computer-aided rational based design on human leukocyte antigen-derived peptides [177], has been discovered to suppress the T-helper 1 cytokine profile, decrease production of inflammatory cytokines including tumor necrosis factor-, interferon-, interleukin-2 and interleukin-12 in both cell lines and animal models [26,178,179]. Several clinical trials on human including phase I safety in normal volunteers, phase II mild-moderate active ulcerative colitis, phase II moderate active ulcerative colitis and phase IICrohn's disease had been completed (Genzyme Corporation; Sanofi, Bridgewater, NJ).…”
Section: Commercial Potential Of Milk Derived Proteins and Peptidesmentioning
confidence: 99%